The Effectiveness of Using Quizizz as a Tool in Developing Student’s Reading Comprehension - Nurul Fatwa; Ernita Daulay (Didaktika: Jurnal Kependidikan, 2024)
The objective of this study is to determine if Quizizz is a useful tool for developing student's reading comprehension for higher education. The present study employs a quantitative research methodology to examine the proposed research issue. The sample size for the 2020 academic year consisted of 30 students majoring in English education, selected using purposive random sampling by the researchers. The paired sample t-test indicated a substantial improvement in students' reading comprehension after the researchers administered treatment, with a p-value of 0.000 < 0.05. The results demonstrate that the use of Quizizz as a teaching tool in the classroom has an important beneficial effect on students' reading comprehension skills.